PEMBUATAN HAND SANITIZER ALAMI DI DESA NAMU UKUR UTARA - Juandi Al Gani Sika; Linda Eriri; Novi Novera; Qur’ani Awaliyana; Ziana Syahputri; Amal Hayati (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
The increasing outbreak of Covid-19 is a serious epidemic that is being faced by the people of Indonesia, so it is mandatory to implement the "5M" namely washing hands, wearing masks, maintaining distance, staying away from crowds, and reducing mobility. Nowadays people prefer to use Hand Sanitizer because it is easier and more practical. The purpose of this research is to conduct counseling in the manufacture of natural hand sanitizers by utilizing natural ingredients, namely betel leaf and lime, with an effort to overcome the soaring prices and production of hand sanitizers on the market. In addition, so that people get an understanding of the manufacture of Hand Sanitizer with natural ingredients. The results obtained in this study were in the form of a natural hand sanitizer made from 70% alcohol 300 ml, 150 grams of betel leaf, and lime juice which was useful as an application to prevent the transmission of Covid-19.